Lipidomic Remodeling in Begonia grandis Under Heat Stress - Sun, Ai-Zhen; Chen, Li-Sha; Tang, Ming; Chen, Juan-Hua; Li, Han; Jin, Xue-Qi; Yi, Yin; Guo, Fang-Qing (Frontiers in Plant Science, 2022)
Characterization of the alterations in leaf lipidome in Begonia (Begonia grandis Dry subsp. sinensis) under heat stress will aid in understanding the mechanisms of stress adaptation to high temperature stress often occurring during hot seasons at southern areas in China. The comparative lipidomic analysis was performed using leaves taken from Begonia plants exposed to ambient temperature or heat stress. The amounts of total lipids and major lipid classes, including monoacylglycerol (MG), diacylglycerol (DG), triacylglycerols (TG), and ethanolamine-, choline-, serine-, inositolglycerophospholipids (PE, PC, PS, PI) and the variations in the content of lipid molecular species, were analyzed and identified by tandem high-resolution mass spectrometry. Upon exposure to heat stress, a substantial increase in three different types of TG, including 18:0/16:0/16:0, 16:0/16:0/18:1 and 18:3/18:3/18:3, was detected, which marked the first stage of adaptation processes. Notably, the reduced accumulation of some phospholipids (PI, PC and PG) was accompanied by an increased accumulation of PS, PE and PA under heat stress. In contrast to the significant increase in the abundance of TG, all of the detected lysophospholipids and sphingolipids were dramatically reduced in the Begonia leaves exposed to heat stress, suggesting that a very dynamic and specified lipid remodeling process is highly coordinated and synchronized in adaptation to heat stress in Begonia plants.